Respon Pertumbuhan Tanaman Pakcoy (Brassica rapa L.) Varietas Nauli F1 Melalui Pemberian Pupuk Kandang Sapi dan NPK 16-16-16 - Hulu, Nidar Mawati; Zulfida, Ida; Dewi, Dora Silvia (UNIVERSITAS LABUHANBATU, 2024)
Pakcoy (Brassica rapa L.) is a type of vegetable plant that belongs to the Brassicaceae family. Pakcoy plants originate from China and have been cultivated since the 5th century widely in southern China and central China and Taiwan. The purpose of this study was to determine the response of growth and yield of pakcoy mustard plants (Brassica rapa L.) through the provision of organic fertilizer Cow Manure and Inorganic fertilizer NPK 16-16-16. This study used a Randomized Block Design (RAK), consisting of 2 factors and 4 levels with 3 Replications. Where the first factor is Cow Manure (P) with 4 levels, namely = P0 Control P1: (1 kg/plot), P2: (2 kg/plot), P3: (3 kg/plot). And the second factor is NPK 16-16-16 fertilizer with 4 levels, namely: N0: control, N1: (25 grams/plot), N2: (50 grams/plot), N3: (75 grams/plot). The parameters observed are: plant height (cm), number of leaves (strands). Analysis of variance with Analysis of variance (Anova), continued with DMRT test at 0.05% level if there is a real treatment. The average height of pak choy plants that gave the highest value was in treatment P2 = 19.15, N0 = 17.72 In the 28th observation hst, the number of leaves in treatment P1 = 114.21, N2 = 12.49. Keywords: pakcoy, cow manure, NPK 16-16-16.